Fetal rhd genotyping from maternal plasma in a population with a highly diverse ethnic background - Machado,Isabela Nelly (2006)
OBJECTIVE: To establish the performance of conventional PCR as a noninvasive method for fetal genotyping, by free fetal DNA analysis of distinct RHD regions from maternal plasma, in a population of a diverse ethnic origin. METHODS: We conducted a validity of the diagnostic test by analyzing 81 plasma samples from RhD-negative Brazilian pregnant women, from 4 to 41 gestational weeks. We tested for exon 10 and intron 4 gene regions by allele specific-PCR. Fetal RHD genotyping by PCR on maternal plasma was compared to serologic RhD typing in the neonatal period. RESULTS: Samples were obtained as follows: 15 in the 1st, 37 in the 2nd and 29 in the 3rd trimester. General accuracy was 97.3%, sensitivity of 98.3% and specificity of 93.8%. CONCLUSIONS: Conventional PCR is an accurate method for fetal RHD genotyping on maternal plasma, even in a population of mixed ethnic origin.